Countercyclical Fiscal Policy and Gender Employment : Evidence from the G-7 Countries - Akitoby, Bernardin (IMF Working Papers; Working Paper ;, 2019)
Would countercyclical fiscal policy during recessions improve or worsen the gender employment gap? We give an answer to this question by exploring the state-dependent impact of fiscal spending shocks on employment by gender in the G-7 countries. Using the local projection method, we find that, during recessions, a positive spending shock of 1 percent of GDP would, on average, lift female employment by 1 percent, while increasing male employment by 0.6 percent. Consequently such a shock would improve the female share of employment by 0.28 percentage point during recessions. Our findings are driven by disproportionate employment changes in female-friendly industries, occupations, and part-time jobs in response to fiscal spending shocks. The analysis suggests that fiscal stimulus, particularly during recessions, could achieve the twin objectives of supporting aggregate demand and improving gender gaps.